2018
DOI: 10.1111/obr.12720
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacologic therapy to induce weight loss in women who have obesity/overweight with polycystic ovary syndrome: a systematic review and network meta‐analysis

Abstract: Liraglutide appears superior to the other drugs in reducing weight and waist circumference.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(38 citation statements)
references
References 75 publications
(163 reference statements)
1
32
1
2
Order By: Relevance
“…It has various physiological effects, including improving insulin resistance, inhibiting appetite and food intake, delaying gastric emptying and reducing body weight (Andersen et al, 2018). Some studies have shown that GLP-1 receptor agonists are superior to metformin for controlling body weight (Elkind-Hirsch et al, 2008;Jensterle et al, 2014;Wang et al, 2018), improving metabolic disorders and menstrual frequency, and significantly increasing the natural pregnancy rate in patients with PCOS (Liu et al, 2017). However, as these studies had small sample sizes and different quality levels, their conclusions differed.…”
mentioning
confidence: 99%
“…It has various physiological effects, including improving insulin resistance, inhibiting appetite and food intake, delaying gastric emptying and reducing body weight (Andersen et al, 2018). Some studies have shown that GLP-1 receptor agonists are superior to metformin for controlling body weight (Elkind-Hirsch et al, 2008;Jensterle et al, 2014;Wang et al, 2018), improving metabolic disorders and menstrual frequency, and significantly increasing the natural pregnancy rate in patients with PCOS (Liu et al, 2017). However, as these studies had small sample sizes and different quality levels, their conclusions differed.…”
mentioning
confidence: 99%
“…The most commonly used outcome variables to measure the effects of nonpharmacological interventions were body weight, BMI, pregnancy rate, waist circumference, and the live birth rate, in-line with the primary outcome variables used to confirm the effects of pharmacological interventions [ 55 , 56 , 57 , 58 ]. This means that nonpharmacological interventions for overweight and obese infertile women focus on eliciting positive effects on actual weight loss and, ultimately, on pregnancy and birth, just like pharmacological interventions.…”
Section: Discussionmentioning
confidence: 99%
“…A network meta-analysis found that the amount of weight loss differed significantly according to the choice of drugs (in descending order): liraglutide, orlistat, and metformin. Liraglutide alone, liraglutide/ metformin, and metformin alone significantly reduced waist circumference, but no change was found with orlistat, indicating liraglutide appears superior to the other drugs in reducing weight and waist circumference (Wang et al, 2018b). IVF, as a choice for more than 1 000 000 infertile couples each year, gives rise to the birth of over 3 000 000 babies worldwide.…”
Section: Towards a Multidimensional Scientific Approach To Improve CLmentioning
confidence: 92%